1983
DOI: 10.3758/bf03205907
|View full text |Cite
|
Sign up to set email alerts
|

Duration discrimination of empty time intervals marked by intermodal pulses

Abstract: In 1973, Rousseau and Kristofferson reported that short empty intermodal time intervals marked by a light flash and a brief tone were poorly discriminated by subjects, and that 4T 75 was constant overa large range of durations. It led them to suggest that short intramodal empty intervals, marked by stimuli from the same sensory modality, might be handled by a "more efficient mechanism" to whichintermodal intervals would not have access. Unfortunately, their study lacked the basic evidence needed to make a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
42
5
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 24 publications
12
42
5
2
Order By: Relevance
“…The only significant main effect was for duration [F(2,44) = 3.69, P < .05]. This finding is consistent with the results of Experiments 1-2 and with those reported by Rousseau et al (1983) for AV intervals. None of the interactions were significant.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The only significant main effect was for duration [F(2,44) = 3.69, P < .05]. This finding is consistent with the results of Experiments 1-2 and with those reported by Rousseau et al (1983) for AV intervals. None of the interactions were significant.…”
Section: Methodssupporting
confidence: 83%
“…The finding that duration discrimination is affected by marker order has been previously observed by Rousseau et al (1983) for intervals of 925 and 1,075 msec. In that study, the duration of VA intervals was generally found to be easier to discriminate than was the duration of AV intervals.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Admittedly, bimodal intervals accessing a central clock more "directly" would lead to optimal performance. Surprisingly, in duration-discrimination tasks, performance levels obtained under bimodal conditions have been shown to be much lower than those obtained with empty unimodal, auditory, or visual time intervals (Fraisse, 1952;Grondin & Rousseau, 1991;Hocherman & Ben-Dov, 1979;Rousseau, Poirier, & Lemyre, 1983). At first view, such findings can be interpreted as detrimental to the notion of a central clock concept.…”
mentioning
confidence: 70%
“…Sensory latencies were found to affect duration judgments (Grondin & Rousseau, 1991;Rousseau, Poirier, & Lemyre, 1983;Grondin, Ivry, Franz, Perreault, & Metthè, 1996). Grondin and Rousseau (1991) found that when a brief beep marked the onset of an interval and a brief light flash marked the offset, the interval was perceived to be longer than when the onset was marked by a light flash and the offset by a beep.…”
Section: Introductionmentioning
confidence: 99%